Arousal in Nocturnal Consciousness: How Dream- and Sleep-Experiences May Inform Us of Poor Sleep Quality, Stress, and Psychopathology - Soffer-Dudek, Nirit (Frontiers in Psychology, 2017)
The term “sleep experiences”, coined by Watson (2001), denotes an array of unusual nocturnal consciousness phenomena; for example, nightmares, vivid or recurrent dreams, hypnagogic hallucinations, dreams of falling or flying, confusional arousals, and lucid dreams. Excluding the latter, these experiences reflect a single factor of atypical oneiric cognitions (“general sleep experiences”). The current study is an opinionated mini-review on the associations of this factor—measured with the Iowa sleep experiences survey (ISES, Watson, 2001)—with psychopathological symptoms and stress. Findings support a strong relation between psychological distress and general sleep experiences. It is suggested that that they should be viewed as a sleep disturbance; they seem to represent involuntary intrusions of wakefulness into sleep, resulting in aroused sleep. These intrusions may stem from excessively thin boundaries between consciousness states (e.g., “transliminality”), or, conversely, they may follow an attempt at disconnecting mental elements (e.g., dissociation), which paradoxically results in a “rebound effect”. The extent to which unusual dreaming is experienced as intrusive, rather than controlled, may explain why general sleep experiences are related to psychopathology, whereas lucid dreams are related to psychological resilience. In conclusion, the exploration of the interplay between psychopathology and sleep should be expanded from focusing almost exclusively on quantitative aspects (e.g., sleep efficiency, latency) to including qualitative conscious experiences which may reflect poor sleep quality. Taking into account nocturnal consciousness—including unusual dreaming and permeable sleep-wake boundaries—may unveil rich information on night-time emotional states and broaden our definition of poor sleep quality.